A guideline for placement of an infra-acetabular screw based on anatomic landmarks via an intra-pelvic approach - Florian Baumann; Paul Schmitz; Daniel Mahr; Maximilian Kerschbaum; Axel Gänsslen; Michael Nerlich; Michael Worlicek (Journal of Orthopaedic Surgery and Research, 2018)
Abstract Background Due to demographic changes, more and more fracture patterns involving anterior acetabular structures occur. The infra-acetabular screw is seen a useful tool to increase stability in fixation of the acetabular cup. However, the exact position of this screw in relation to anatomic landmarks which are intra-operatively palpable via an intra-pelvic approach has not yet been determined. Methods This biomorphometric experimental study references the ideal screw position of an infra-acetabular screw to anatomic landmarks palpable via an intra-pelvic approach. Therefore, we created a computer tomography-based 3D-model of 40 patients (20 women, 20 men) who received a computer tomography (CT) scan of the pelvis for any other reason than an acetabular fracture. Results The entry point of an ideal infra-acetabular was of high constancy. At mean, this point was 10.2 mm caudal and 10.4 mm medial of the ilio-pubic/ilio-pectineal eminence. This reference is independent of age, gender, or physical dimensions. However, we found gender-dependent differences for the angulation and the length of the screw. Conclusions This study provides a comprehensive guideline to determine the ideal entry point for an infra-acetabular screw via an intra-pelvic approach. The entry point is located 10.2 mm caudal and 10.4 mm medial of the ilio-pubic/ilio-pectineal eminence. Trial registration Clinical Trial Registry University of Regensburg Z-2017-0930-1. Registered 04. Dec 2017.